2017
DOI: 10.5152/tud.2017.66502
|View full text |Cite
|
Sign up to set email alerts
|

Metabesity and urological cancers

Abstract: Metabolic syndrome is one of today's most important health problems. Due to increased prevalence of metabolic syndrome in society, studies done on this topic have increased in number. Although metabolic syndrome was previously considered to be important only for cardiovascular health, it has been learned that with new data, human health is compromised more thoroughly by metabolic syndrome and is also a danger to malignancy. As a result, a new definition in the form of metabesity has been introduced. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Collectively, DNP may be a treatment for an emerging global term called “metabesity” referring to all the co-morbidities associated with the over-nutritional phenotype such an increased incidence of insulin resistance, obesity, type 2 diabetes, sleep apnea, depression, inflammation, cardiovascular disease, hypertension, non-alcoholic fatty liver disease , but includes accelerated aging, neurodegeneration, and cancer. [2,184,185]. Studies are underway to explore an ever-expanding application of low dose mitochondrial uncoupling pharmacology.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…Collectively, DNP may be a treatment for an emerging global term called “metabesity” referring to all the co-morbidities associated with the over-nutritional phenotype such an increased incidence of insulin resistance, obesity, type 2 diabetes, sleep apnea, depression, inflammation, cardiovascular disease, hypertension, non-alcoholic fatty liver disease , but includes accelerated aging, neurodegeneration, and cancer. [2,184,185]. Studies are underway to explore an ever-expanding application of low dose mitochondrial uncoupling pharmacology.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…With the increasing prevalence of MetS, the number of studies on MetS etiology and MetS -related diseases has also increased. Considering that MetS and its components should be evaluated in a broader spectrum, a concept termed metabesity has been introduced with the increasing recognition of their relationship with cancer [16]. In our study, it was concluded that the patients with MetS had a larger tumor size and a higher Fuhrman grade than those without MetS, but there was no difference between the two groups in terms of the pathological stage.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, Dr. Alexander Fleming who is an endocrinologist added a different dimension to the definition of metabolic syndrome by introducing the concept of metabesity (2013). According to Dr. Fleming, metabesity describes all relevant conditions (diabetes mellitus, obesity, metabolic syndrome, cardiovascular disease, dyslipidaemia≥, cancer promoting factors and accelerated aging) which impose a serious burden on healthcare, and economic state [23].…”
Section: Introductionmentioning
confidence: 99%